Bacterial biofilm on PLA film and methods of its identification - Richert, Agnieszka; Dąbrowska, Grażyna B. (Ecological Questions, 2020)
This paper presents a brief characterization of bacterial biofilm, formed on polylactide, ecologically important biodegradable material. The concept of bacterial biofilm was explained, including the process of its formation as well as the structure and model of functioning in a biological environment. Three methods of its determination and documentation by spectrophotometric measurement, live/dead test using fluorescence microscope and surface structure analysis using scanning electron microscope were presented.